Pengaruh Dana Pihak Ketiga, CAR, NPF dan FDR terhadap ROA pada Bank Syariah yang Terdaftar pada Bursa Efek Indonesia - Devira Sari Pradina Putri; Purwohandoko Purwohandoko (Inspirasi Nusantara, 2021)
The aim of this study is to the development of Islamic finance in Indonesia is important to continue and profitability is important for develop of islamic finance. This researchdetermine to analyze the effect Third Party Funds, Capital Adequacy Ratio (CAR), Non-Performing Finances (NPF), and Financing to Deposit Ratio (FDR) to Return on Asset (ROA) of syariah banks listed on Indonesia Stock Exchange (BEI) during periods 2017-2018. This research uses explanatory research and the sample uses purposive sampling about 11 syariah banks. The analysis method used multiple linear regression analysis include classical asuumption test, and hypothesis test with SPSS version 22. The test result showed that DPK, CAR and FDR has no effect on ROA, meanwhile NPF has effect on ROA of syariah bank in Indonesia. This results shows that NPF has significant role to increase financial assets so that this can be attract for customer and investor to saving or control their funds.